Students’ Perceptions on Self-Assessment in Writing Competency at Senior High School - Putu Veni Aryanti; Ni Luh Putu Eka Sulistia Dewi; Wahyuni, Luh Gede Eka; Anak Agung Gede Yudha Paramartha (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
The current situation, which has entered the digital era, has a close relationship with understanding character for a person. Self-assessment is an assessment process in which a person is asked to assess himself with regard to the status, process, and level of achievement of the competencies he has learned. This research aims to analyze and understand students’ perceptions regarding the use of self- assessment in their writing competence and the challenges that make it difficult for mov them to do. In this research, the method used was a survey with a qualitative approach while the subjects of this research were students in grades 10 and 11 from Senior high school. Data collection took the form of a questionnaire via a Google Form link and interviews conducted online. Data analysis conducted thematic analysis analyzing qualitative data to describe and interpret. The results of this research state that students tend to have positive perceptions regarding the use of self-assessment contained in writing competency. So that students can be more confident, achieve their desires and motivate themselves to use self-assessment as an evaluation in learning to improve the quality of writing skills. However, there are also challenges when using self-assessment in learning that make students feel difficult, such as assessing their own and not understanding the criteria for self-assessment.